Effect of microwave pre-treatment for hydrodistillation extraction on essential oil yield from indigenous herb, Physalis Minima Linn - Uda, Nor Fatimah (2019)
The common method used to extract the beneficial contents of the plant was by using the extraction technique. Physalis Minima Linn or known as "Pokok Letup" in Malaysia was categorized as a medicinal plant by many region and country especially in India. This plant contain several phytochemical that been beneficial to human health. In this study, the type of extraction method used was hydrodistillation extraction technique. In order to achieve the first objective, to identify the phytochemical content in this plant, the GC-MS analysis was done and for the second objective, to study the parameter that affected the extraction yield, three parameter had been manipulated which are pre-treatment power, that varies firom 180W to 540W (180W, 270W, 360W, 450W and 540W), next parameter was extraction time. The extraction time was varied from 30min to 150min (30min, 60min, 90min, 120min and 150min) and the last parameter was pre-treatment time that varies from 3Os to 120s (3Os, 60s, 90s and 120s). The result obtained from this study, four compound had been identified from GC-MS analysis which were diethyl phthalate (5.296%) which inhibits the color and odor of the oils besides that carry the anti-fertility element, next compound was aristolene (1.063%) which inhibits the cytotoxic of the plant, the third compound was ibuprofen (0.994%) inhibits the antiinflammatory element and the last compound was Cyclononasiloxane, Octadecamethyl- (0.127%>). For the extraction oil yield, for the first parameter, which was effect of pre-treatment power, the highest yield was 27.6% at 540W and the lowest was 19.5% at 180W. Next, for the effect of extraction time, the highest yield was 24.4% at 150min extraction time and lowest at 30min extraction time which yield was 4%. For the effect of pre-treatment time, the highest yield was 21.3% which was at 60s of pre-treatment time and lowest yield was 18.3% at 30s pre-treatment time. So, the optimum parameter for this study was pre-treatment power of 540W, 60s of pre-treatment time and 150min of extraction time.